2014
DOI: 10.1002/chem.201402089
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Tetrahydroquinolines through a [3+2] Cycloaddition Controlled by Dienamine Catalysis

Abstract: A dienamine-mediated enantioselective 1,3-dipolar cycloaddition catalyzed by a chiral prolinol silyl ether catalyst has been developed. Removal of the benzamide group of the intermediates could furnish chiral C-1 substituted tetrahydroisoquinolines (see scheme) in high yields and excellent stereoselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 52 publications
0
25
1
Order By: Relevance
“…In the presence of pyrrolidine‐type organocatalysts 6 , the enantioselective [3+2] dipolar cycloaddition reactions of C,N‐cyclic azomethine imines as dipoles with α,β‐unsaturated aldehydes as dipolarophiles could proceed in two different directions. This dual‐reactivity was independently reported by two research groups in 2014 . Du, Wang and co‐workers used β‐arylmethylenals 110 as substrates in the synthesis of new pyrazole derivatives.…”
Section: Pyrazoles Pyrazolines and Pyrazolidinesmentioning
confidence: 59%
See 2 more Smart Citations
“…In the presence of pyrrolidine‐type organocatalysts 6 , the enantioselective [3+2] dipolar cycloaddition reactions of C,N‐cyclic azomethine imines as dipoles with α,β‐unsaturated aldehydes as dipolarophiles could proceed in two different directions. This dual‐reactivity was independently reported by two research groups in 2014 . Du, Wang and co‐workers used β‐arylmethylenals 110 as substrates in the synthesis of new pyrazole derivatives.…”
Section: Pyrazoles Pyrazolines and Pyrazolidinesmentioning
confidence: 59%
“…The generality of the reaction was evaluated for 17 substrates. However, aliphatic enals 113 gave different [3+2] cycloadducts ( 114 ), as shown in Scheme , Equation (2) . In the authors′ opinion, their formation proceeded through α,β‐unsaturated iminium ion A , which played a key role in triggering the normal‐electron‐demand 1,3‐dipolar cycloaddition reaction.…”
Section: Pyrazoles Pyrazolines and Pyrazolidinesmentioning
confidence: 97%
See 1 more Smart Citation
“…In the latter case, the reaction proceeds via 3,4-reactivity of the iminium ion reactive intermediates. Products 119 were formed in 79–83% yields, dr > 25:1 and 80–94% ee ( Scheme 36 ) [ 60 ].…”
Section: Synthesis Of Pyrazolidinesmentioning
confidence: 99%
“…[14] The pioneering contributions during the past decade have led to the discovery of various highly enantioselective a-, b-, gfunctionalizations and cycloaddition reactions of enals. [14][15][16] Inspired by the synthetic potential of dienamine activation, we investigated the recently designed enaldiazo compounds (diazoenals) [17,18] as precursors for novel dienamines.O ur studies revealed that rhodium-catalyzed reactions of enaldiazo carbonyl compounds with secondary arylamines readily furnishes novel g-amino-substituted donor-acceptor dienamines (Scheme 1b). To the best of our knowledge,this is the first report on the formation of functionalized dienamines through carbenoids.…”
mentioning
confidence: 99%